2022
DOI: 10.3390/ani12152001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Duration of High-Grain Feeding on Chewing, Feeding Behavior, and Salivary Composition in Cows with or without a Phytogenic Feed Supplement

Abstract: Switching diets from forage to a high-grain (HG) diet increases the risk of rumen fermentation disorders in cattle. However, the effects of the duration of the HG feeding, after the diet switch, on animal behavior and health have received considerably less attention. This experiment primarily aimed to assess the effects of the duration of an HG diet on the chewing, eating, and lying behavior and salivation dynamics in a control group (CON) and a group of cows receiving a phytogenic feed supplement (TRT) at 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The chewing behavior was measured during 3 consecutive days in week 3 ap, week 1 ap, and week 7 pp from 00:00 h to 23:59 h using validated rumination halters (RumiWatch System, ITIN + Hoch GmbH, Switzerland; Kröger et al, 2016 ) according to the procedure and the parameters described by Rivera-Chacon et al (2022b) . In brief, all halters were attached to the cows one day before the measurements started to allow the cows to get used to them.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chewing behavior was measured during 3 consecutive days in week 3 ap, week 1 ap, and week 7 pp from 00:00 h to 23:59 h using validated rumination halters (RumiWatch System, ITIN + Hoch GmbH, Switzerland; Kröger et al, 2016 ) according to the procedure and the parameters described by Rivera-Chacon et al (2022b) . In brief, all halters were attached to the cows one day before the measurements started to allow the cows to get used to them.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, a sorting index of 100 indicated no sorting of the particle fraction, whereas a sorting index above indicated that the cows sorted for that fraction and a sorting index below 100 indicated that the cows sorted against that fraction. The diurnal lying behavior of cows was determined on all days in week 2 pp and week 7 pp using data loggers (HOBO Pendant G Acceleration Data Logger, Onset Computer Corp., Bourne, MA) and following the protocol and parameters outlined by Rivera-Chacon et al (2022b) .…”
Section: Methodsmentioning
confidence: 99%